1977
DOI: 10.1007/bf02671040
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐five years of flavor research in a food industry

Abstract: AND SUMMARYIn the last few decades, flavor research has developed along different main routes. The first step was the discovery of the complex mixtures of volatile components that together build the particular flavors. Apart from this, interest became focused on the taste substances which, through interaction with the flavor carriers, impart aroma to a food. The third main route was the investigation of the deterioration in odor and taste due to oxidative or microbial spoilage. As these investigations progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…For example, partial hydrogenation of linolenate in soyabean oil produces isomeric dienes, known as isolinoleic acids. Keppler andcoworkers (1965, 1967) demonstrated that cis,cis-9,15 and 8,15-octadecadienoates are the precursors of an unpleasant 'hardening' flavour that develops during storage of hydrogenated oils. The aldehyde 6-trans-nonenal has been reported to be responsible for this off-flavour (Table 6.3).…”
Section: Aldehydesmentioning
confidence: 99%
“…For example, partial hydrogenation of linolenate in soyabean oil produces isomeric dienes, known as isolinoleic acids. Keppler andcoworkers (1965, 1967) demonstrated that cis,cis-9,15 and 8,15-octadecadienoates are the precursors of an unpleasant 'hardening' flavour that develops during storage of hydrogenated oils. The aldehyde 6-trans-nonenal has been reported to be responsible for this off-flavour (Table 6.3).…”
Section: Aldehydesmentioning
confidence: 99%
“…So basiert z. B. die von KEPPLER [34] beschriebene Lactonproduktion auf der Flhigkeit von Saccharomyces cerevisiae, diese aus Ketosauren zu synthetisieren. Die Bildung von Ethylacetat durch Candida utilis wird bei Ethanolzugabe beschleunigt [6].…”
Section: Biotransformationunclassified
“…Several classes of compounds have been implicated in off-flavor development of deteriorating oils. Flavor descriptions and thresholds were studied for many of these (Evans et al, 1974;Badings, 1960;Keppler, 1977;Selke et al, 1975). Duin (1960) identified the following classes of carbonyls as contributing to offflavor in butter; saturated aldehydes (C^ -C^g), 2-enals (C^ ~^ll^ ' 2,4-dienals (C^ -C^^^), enals with the double bond not in the 2-position (Cg -C^g), and dienals with a double bond in non-conjugated position to the 2-enal configuration (Cg -C^g).…”
Section: R-c-r ^ R-c-r R-c-r + R Oh R-c-r + R R« + R-c=0 R-c-r + R IImentioning
confidence: 99%
“…By mixing 2-ketones at subthreshold levels, a synergistic effect was reported, and thresholds of individual compounds reduced. Keppler (1977) reported threshold values for a number of aldehydes. Values included 0.04 ppm for 2-trans-4-trans-hexadienal, 0.50 ppm for 2-trans-4-trans-heptadienal, and 0.35 ppm for 2-trans-pentenal.…”
Section: R-c-r ^ R-c-r R-c-r + R Oh R-c-r + R R« + R-c=0 R-c-r + R IImentioning
confidence: 99%
See 1 more Smart Citation